A domain decomposition method for the simulation of fracture in polysilicon MEMS - Confalonieri, Federica; Cocchetti, Giuseppe; Ghisi, Aldo; Corigliano, Alberto (Microelectronics and reliability, 2013)
To overcome the computational burden associated to the three-dimensional finite element simulation of fracture phenomena in polysilicon MEMS during dynamic loading, like e.g. impacts, a domain decomposition technique is used. The approach extends a method developed for linear elastic materials, by including cohesive crack propagation and it allows for the simulation of inter and trans-granular fracture initiation and propagation in polycrystals and it is a step forward in the construction of a complete simulation tool for the description of fracture phenomena in microsystems. Applications to critical MEMS details show encouraging results in reproducing local failure mechanisms.